Biomedical signal processing : principles and techniques - Reddy, D. C. (New Delhi : Tata McGraw-Hill, 2005)
This book intended for the first course on "Biomedical Signal Processing", is written in the form of an undergraduate text.It strikes the right balance between the analytical tools required for the developement of the various techniques of digital signal processing and their application in clinical practice.
Chapter 1 Discrete-Time Signals and Systsems -- Chapter 2 The Discrete Fourier Transform -- Chapter 3 Theory of z-Transform -- Chapter 4 Neurological Signal Processing -- Chapter 5 Sleep eeg -- Chapter 6 Adaptive Interference/Noise Cancellation -- Chapter 7 Cardiological Signal Processing -- Chapter 8 Ecg Data Reduction Techniques -- Chapter 9 Prony?s Method
Includes index.
1
Keywords: Signal processing; Biomedical engineering